MENELUSURI JEJAK MAQASHID SYARI’AH DALAM ISTINBATH HUKUM IMAM HAMBALI - Muttaqin, Muhammad Ngizzul; Nur, Iffatin (IAIN Tulungagung, 2019)
ABSTRACTTheoretically, Maqashid Shari’ah puts forward the concepts, objectives and adaptability of Islamic law from philosophical-ideological characteristic to an actual-empirical one. The problems discussed in maqashid shari'ah are always interesting and debatable to Muslim scholars as well as comman people. Therefore, reviewing and tracing the footsteps of maqashid syari’ah in Imam Hambali’s legal method of istimbath has a strategic value in honing intellectual acuity as well as making it as a parameter in formulating new laws on various increasingly complicated and crucial contemporary issues faced by Muslims. In tracing the footsteps of maqashid shari’ah employing Sad Dzari’ah, which is the Hambali’s legal method of istimbath, it appears that flexibility, and dynamism of Islamic law rests on purposefulness (maqashid) as the essence of the law itself.Keywords: Imam Hambali, Islamic law, IstinbathMethod, Maqashid Syari’ah, Sad Dzari’ah